Shallow landslide susceptibility map at a regional scale (Asturias, NW Spain). A heuristic-driven approach - Rosana Menéndez-Duarte; Jorge Marquínez; Daniel Vázquez-Tarrío; Francisco José Fernández (Journal of Maps)
The study area (Asturias, NW Spain) is a mountainous region extending over 10,000 km2, where shallow landslides triggered after heavy rainfall episodes are very frequent and pose a major threat and hazard to infrastructure and human populations, causing frequenteconomic losses and damage. In this regard, Shallow Landslide Susceptibility Mapping (SLSM) represents a very powerful tool for managers and agencies dealing with landslide hazards and land planning. Here we produced an SLSM based on basic geological/geomorphological maps and a heuristic approach. The regional-scale model built here has a cell resolution of 50 m and combines bedrock geology, and surface deposits mapped at a1:25k scale together with a digital slope model. The resulting map was compared with two local inventories of landslides, giving a goodness of fit of 80 and 77.5%. To better understand the results, the erroneous data have been reviewed individually and the causes of error were analysed.